2018
DOI: 10.1016/j.stemcr.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Stem Cells Exhibit Conditional Circadian Clock Function

Abstract: SummaryThe circadian clock is a molecular pacemaker that produces 24-hr physiological cycles known as circadian rhythms. How the clock regulates stem cells is an emerging area of research with many outstanding questions. We tested clock function in vivo at the single cell resolution in the Drosophila intestine, a tissue that is exquisitely sensitive to environmental cues and has circadian rhythms in regeneration. Our results indicate that circadian clocks function in intestinal stem cells and enterocytes but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…The wide range of physiological turnover time reflects the stochastic damage of absorptive enterocytes (ECs)—the main cells in the intestinal epithelium (Biteau et al , ; Jiang & Edgar, )—by exposure to pathogens and toxins present in food and chemicals and physical stress. The intestine also contains secretory enteroendocrine (EE) cells, which constitute only 10% of the intestinal population and renew themselves at a slower rate than ECs (de Navascués et al , ; Sallé et al , ; Parasram et al , ). Intestinal cell turnover is sustained by a small population of ISCs scattered throughout the epithelium that, as observed in other high‐turnover epithelia in mammals (Simons & Clevers, ), divide regularly and produce, with each division, one cell that differentiates and one that remains undifferentiated.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of physiological turnover time reflects the stochastic damage of absorptive enterocytes (ECs)—the main cells in the intestinal epithelium (Biteau et al , ; Jiang & Edgar, )—by exposure to pathogens and toxins present in food and chemicals and physical stress. The intestine also contains secretory enteroendocrine (EE) cells, which constitute only 10% of the intestinal population and renew themselves at a slower rate than ECs (de Navascués et al , ; Sallé et al , ; Parasram et al , ). Intestinal cell turnover is sustained by a small population of ISCs scattered throughout the epithelium that, as observed in other high‐turnover epithelia in mammals (Simons & Clevers, ), divide regularly and produce, with each division, one cell that differentiates and one that remains undifferentiated.…”
Section: Introductionmentioning
confidence: 99%
“…One study that included positive controls [31] did, however, not mention the origin of Caco-2 cells and did not cultivate them on filter inserts. Notably, it was shown that intestinal cells, also Caco-2 cells, are subjected to a circadian rhythm, as they express several important clock genes [63][64][65][66][67]. Moreover, a circadian regulation of the expression of ABCG5/G8 has already been shown in the liver [68], which is very likely to hold true also for the intestine.…”
Section: Discussionmentioning
confidence: 96%
“…Before we end the discussion on homeostasis in intestinal stem cells via microbial metabolites, we would like to highlight another possible role of microbial metabolites in regulating intestinal epithelial renewal—“as a modulator of circadian rhythm.” It is known that mammalian circadian rhythm is maintained by both an intrinsic molecular clock existing in almost every living cell in our body, and an extrinsic synchronization mechanism incorporating diurnal signals such as light/dark condition, temperature variation, and feeding patterns. [ 192,193 ] The intestinal stem cell activities are typically modulated intrinsically by the molecular clock, and extrinsically by insulin levels induced by the feeding condition. [ 192 ] Nevertheless, we speculate that gut microbial metabolites could act as an additional mediator for establishing the circadian patterns in intestinal stem cells.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…[ 192,193 ] The intestinal stem cell activities are typically modulated intrinsically by the molecular clock, and extrinsically by insulin levels induced by the feeding condition. [ 192 ] Nevertheless, we speculate that gut microbial metabolites could act as an additional mediator for establishing the circadian patterns in intestinal stem cells. The gut microbiota is shown to be influenced by the circadian rhythm through the host molecular clock and extrinsic signals, particularly by feeding patterns.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%